Evaluation of Factors Affecting Perinatal Mortality in Patients with HELLP Syndrome - Gunduz, Reyhan; Yaman Tunc, Senem; Icen, Mehmet Sait; Ertugrul, Sabahattin; Gul, Talip (Gynecology Obstetrics & Reproductive Medicine, 2021)
OBJECTIVE: To determine the perinatal mortality rate in patients with HELLP syndrome in our clinic and to investigate the factors affecting perinatal mortality. It also makes recommendations to reduce perinatal mortality and contributes to the literature. STUDY DESIGN: Three-hundred-and-eighty-three patients were retrospectively evaluated in this cohort study. The patients' demographic, clinical data, laboratory results, gestational week at delivery, method of delivery, neonatal birth weight, fetal gender, 1- and 5-minute APGAR scores, place of delivery, maternal morbidity, mortality rates, and perinatal mortality rates were recorded. The relationship of these factors with perinatal mortality was investigated. RESULTS: The rate of perinatal mortality was determined as 6%. Patients with HELLP syndrome who experienced perinatal mortality showed significantly lower birth weight, gestational age at delivery, and 1- and 5-minute APGAR score values (p<0.05). With respect to methods of delivery, we determined that vaginal delivery was linked to a significantly higher rate of perinatal mortality (p<0.001). Gestational age at delivery, birth weight, 1- and 5-minute APGAR scores were negatively correlated with perinatal mortality. Logistic regression revealed the APGAR score at 5 minutes as the most reliable independent predictive finding for perinatal mortality. CONCLUSION: We think that to decrease perinatal mortality rates, maternal and fetal well-being in patients with HELLP syndrome should be closely monitored and delivery and follow-up should take place at tertiary health institutions after maternal and neonatal intensive care arrangements are made. Particularly, neonates with low 5-minute APGAR scores in the postpartum evaluation of neonatal condition are recommended to be followed-up at the neonatal intensive care unit.